Comparison of Different Electrocardiography with Vectorcardiography Transformations - Jaros, Rene; Martinek, Radek; Danys, Lukas (Sensors (Basel, Switzerland), 2019)
This paper deals with transformations from electrocardiographic (ECG) to vectorcardiographic (VCG) leads. VCG provides better sensitivity, for example for the detection of myocardial infarction, ischemia, and hypertrophy. However, in clinical practice, measurement of VCG is not usually used because it requires additional electrodes placed on the patient's body. Instead, mathematical transformations are used for deriving VCG from 12-leads ECG. In this work, Kors quasi-orthogonal transformation, inverse Dower transformation, Kors regression transformation, and linear regression-based transformations for deriving P wave (PLSV) and QRS complex (QLSV) are implemented and compared. These transformation methods were not yet compared before, so we have selected them for this paper. Transformation methods were compared for the data from the Physikalisch-Technische Bundesanstalt (PTB) database and their accuracy was evaluated using a mean squared error (MSE) and a correlation coefficient (R) between the derived and directly measured Frank's leads. Based on the statistical analysis, Kors regression transformation was significantly more accurate for the derivation of the X and Y leads than the others. For the Z lead, there were no statistically significant differences in the medians between Kors regression transformation and the PLSV and QLSV methods. This paper thoroughly compared multiple VCG transformation methods to conventional VCG Frank's orthogonal lead system, used in clinical practice.
Keywords: transformation; Databases, Factual; Linear Models; Diagnosis, Computer-Assisted; lidé; Vectorcardiography; vektorkardiografie; elektrokardiografie; diagnóza počítačová; databáze faktografické; electrocardiography; matematické výpočty počítačové; Humans; Frank’s leads; least-squares fit method; dower transformation; Signal Processing, Computer-Assisted; počítačové zpracování signálu; Mathematical Computing; Electrocardiography; Kors transformation; vectorcardiography; Heart Diseases; quasi-orthogonal leads; lineární modely; nemoci srdce